Physician champions' perspectives and practices on electronic health records implementation: challenges and strategies. Issue 1 (7th January 2020) - Gui, Xinning; Chen, Yunan; Zhou, Xiaomu; Reynolds, Tera L; Zheng, Kai; Hanauer, David A
Abstract: Objective: Physician champions are "boots on the ground" physician leaders who facilitate the implementation of, and transition to, new health information technology (HIT) systems within an organization. They are commonly cited as key personnel in HIT implementations, yet little research has focused on their practices and perspectives. Materials and Methods: We addressed this research gap through a qualitative study of physician champions that aimed to capture their challenges and strategies during a large-scale HIT implementation. Email interviews were conducted with 45 physician champions from diverse clinical areas 5 months after a new electronic health record (EHR) system went live in a large academic medical center. We adopted a grounded theory approach to analyze the data. Results: Our physician champion participants reported multiple challenges, including insufficient training, limited at-the-elbow support, unreliable communication with leadership and the EHR vendor, as well as flawed system design. To overcome these challenges, physician champions developed their own personalized training programs in a simulated context or in the live environment, sought and obtained more at-the-elbow support both internally and externally, and adapted their departmental sociotechnical context to make the system work better. Discussion and Conclusions: This study identified the challenges physician champions faced and the strategies they developed to overcome these challenges. Our findings suggest factors that are crucial to the successful involvement of physician champions in HIT implementations, including the availability of instrumental (eg, reward for efforts), emotional (eg, mechanisms for expressing frustrations), and peer support; ongoing engagement with the champions; and appropriate training and customization planning.